Effects of supplemental different clay minerals in broiler chickens under cyclic heat stress - Jaewoo An; Jihwan Lee; Minho Song; Hanjin Oh; Yongju Kim; Seyeon Chang; Youngbin Go; Dongcheol Song; Hyunah Cho; Haeryoung Park; Hyeun Bum Kim; Jinho Cho (Journal of Animal Science and Technology, 2023)
The objective of this study was to investigate the effect of supplementing clay minerals and organic chromium in feed on broiler chicken under heat stress (HS). A total of 90 one-day-old broiler chicken (Arbor Acres) with an initial body weight of 45.0 ± 0.2 g were assigned to five treatment groups (six replications, three birds each cage): 1) NC group, basal diet under room temperature environment; 2) PC group, basal diet under high temperature (HT) environment; 3) ILT group, basal diet + 1% illite + HT; 4) ZLT group, basal diet + 1% zeolite + HT; 5) OC group, basal diet + 400 ppb/kg organic chromium + HT. The ILT and ZLT groups had significantly higher body weight than the PC group in 4 weeks. Apparent total tract digestibility of gross energy was increased in the ILT, ZLT, and OC groups compared to the PC group. The NC group had lower foot-pad dermatitis score than other groups. Escherichia coli population in the cecum and feces was decreased in the ZLT group than in the PC group. Lactobacillus in cecum and feces was significantly increased in the ZLT group than in the PC group. Regarding blood profiles, blood cortisol was decreased in the NC and ILT groups compared to the PC group. Water holding capacity and pH were increased in the ZLT group than the PC group. In conclusion, according to the results of growth performance, nutrients digestibility, bacteria counts, and meat characteristics, supplementation of the ZLT in broiler diet can alleviate HS.